Estudo sobre a não-extensividade associada ao Quasar 3C 273 por meio da análise espectro-temporal de suas curvas de luz - Alencar Filho, Francisco Valdo (2022)
Quasars are one of the most intriguing and fascinating cosmic objects in the universe. Today, it is known that they constitute one of the possible types of a structure known as the Active Galaxy Nuclei (AGN), which harbors a supermassive black hole in its interior. Discovered in the early 1960s, quasars proved to be objects of difficult study and identification, as they were originally detected as a weak light source seen in the optical range, but which had an enormous radiative abundance in the radio range and large variability when viewed on X-rays. The quasar 3C 273, object of this study, was the first to have its spectrum identified, and it has the largest amount of observational data known. Using the Matlab language, we performed a spectro-temporal analysis of the light curves of 3C 273 in an attempt to discover how this object behaves seen in different bands of the electromagnetic spectrum. We believe that the non-extensive formalism of statistical mechanics developed by the physicist C.Tsallis provides a robust mathematical tool for describing the behavior and properties exhibited by this object, and, as a result, we show the relationship between the energy E of radiation and the entropy index, q. Therefore, our objective is to show the behavior of the entropic index q seen in different bands, since this parameter is directly related to the tail extension of our distributions, which, in turn, can be related to a given physical phenomenon associated that frequency range. Through the mentioned procedure, we were able to find a correlation between some spectrum bands, and this can be an indication that the same physical mechanism operates in these frequency/energy bands. Finally, we show that non-extensive statistical mechanics is, in fact, the theory that best fits the behavior of this cosmic object, and the results presented here can be generalized in studies that analyze the spectrum of other celestial objects.